What promotes sustained return to work of employees on long-term sick leave? Perspectives of vocational rehabilitation professionals - Patricia M Dekkers-Sánchez; Haije Wind; Judith K Sluiter; Monique HW Frings-Dresen (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: The aim of this study was to (i) explore promoting factors for sustained return to work (RTW), according to vocational rehabilitation professionals (VRP) that are amenable to change for employees who have been on sick leave >18 months and (ii) gain insight into crucial aspects of interventions. Methods Semi-structured interviews were carried out with 23 VRP. All interviews were transcribed fully verbatim. An inductive analysis of the transcripts was performed, using a process of identifying, coding, and categorizing the primary patterns in the data. RESULTS: Key influenceable promoting factors for sustained RTW by long-term sick-listed employees include: employee-based vocational guidance; integral, effective communication between the sick-listed employee and all RTW stakeholders; personal factors; a supportive work environment; and a stimulating social environment. Crucial aspects of interventions include: gathering information and setting priorities; improving qualifications; influencing cognitions; monitoring the sick-listed employee through the rehabilitation process; offering tailor-made interventions at different stages within a personal time-bound action plan; and preparing the employee and the work environment for RTW. CONCLUSIONS: Sustained RTW for long-term sick-listed employees can be achieved by focusing on the influenceable promoting factors for RTW. The use of combined interventions in a holistic approach involving the worker and his environment is considered the best way to address the multicausality of work disability and could help maximize RTW outcomes.